1994
DOI: 10.1111/j.1540-8167.1994.tb01124.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of a Nodofascicular Connection in Supraventricular Tachycardia with VA Dissociation

Abstract: We present the case of a patient with episodes of supraventricular tachycardia and atrial dissociation that were terminated by either adenosine or verapamil. Involvement of an accessory pathway was shown by ventricular extrastimuli, elicited during His-bundle refractoriness, that interrupted the tachycardia or advanced the next His potential. The tachycardia circuit was demonstrated to be confined to the nodofascicular region based on the exclusion of surrounding tissues. Atrial activity, including that in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 31 publications
1
42
2
Order By: Relevance
“…Reversal of the depolarization sequence of the His and the right bundle branch potentials was observed by Haissaguerre et al [68]. During ventricular pacing the right bundle branch potential preceded the recording of the His bundle potential.…”
Section: Retrograde Vh Conductionmentioning
confidence: 85%
See 3 more Smart Citations
“…Reversal of the depolarization sequence of the His and the right bundle branch potentials was observed by Haissaguerre et al [68]. During ventricular pacing the right bundle branch potential preceded the recording of the His bundle potential.…”
Section: Retrograde Vh Conductionmentioning
confidence: 85%
“…Since the 1980s, when it became clear that the majority of the previously called nodoventricular fibers were in reality atriofascicular pathways, some authors even doubted the very existence of such structures. In the last 25 years we have learned that nodoventricular and nodofascicular fibers do exist, but only a few well-studied cases were reported [60][61][62][63][64][65][66][67][68][69][70][71][72][73][74]. Nodoventricular fibers were recently described in the autopsy of a patient who had a PRKAG2 gene mutation.…”
Section: Nodoventricular and Nodofascicular Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…It is not possible to preexcite ventricular activation, because the AP is taking off from the AV node. [9][10][11][12] Those cases showed no preexcitation at baseline ECG and a narrow QRS tachycardia with ventriculoatrial block or AV dissociation, and a midseptal concealed NF/NV fiber was successfully ablated. However, Porkolab et al 55 showed failure of decremental right atrial Figure 13.…”
Section: Fv Fibersmentioning
confidence: 99%